Prepared to launch? A study of Thailand's New Entrepreneurs' Creation (NEC) education program - Ronda M. Smith; Poompichai Tarndamrong; Terrence C. Sebora; Charlie A. Wolfe (The International Journal of Management Science and Information Technology (IJMSIT), 2015)
Facilitating the rate of new venture creation is an important goal of many governmental organizations. The goal of this study was to explore the effectiveness of a specific program, the New Entrepreneu's Creation (NEC) program being administered by the Thai government at 12 institutions in Bangkok, Thailand. In this study, 389 participants were recruited and surveyed from the 2008 training class of the NEC. In addition to examining founding intentions, this study assessed four cognitive measures that are likely to influence an individual's perception of his or her preparedness to start a business among participants in Thailand's New Entrepreneur Creation (NEC) education program. These include: entrepreneurial understanding, knowledge of entrepreneurial skills, entrepreneurial attitudes/beliefs, and entrepreneurial self-efficacy. Entrepreneurial understanding measures basic knowledge of entrepreneurship, the role of entrepreneurs and profit in the economy. Knowledge of entrepreneurial skills assesses the awareness of skills needed during the founding process, such as leadership, persistence, and market opportunity identification. Entrepreneurial attitudes and beliefs assess how perceptions of social status and career satisfaction associated with starting a new venture. Entrepreneurial self-efficacy measures participants' confidence in their abilities to carry out startup and venture founding activities, such as risk management and internal business operations. The government sponsored NEC program appears to enhance the desire of the participants to become entrepreneurs but might not provide enough concrete information to develop the requisite understanding and skill needed to actually start a business. These findings suggest that public policy initiatives might be better served by bolstering training that facilitates hands-on business creation skills in addition to developing or reinforcing self-efficacy about the process. These implications should provide a platform from which relevant parties can begin to strengthen efforts to develop both entrepreneurial understanding and entrepreneurial skill in aspiring Thai entrepreneurs. It is not sufficient that participants just enhance their confidence in their abilities to start a business; rather they must also acquire necessary skills and abilities. Enhancements in these areas are argued to increase the likelihood that new ventures may actually be founded, which is the ultimate goal of the program.
Keywords: 650; Entrepreneurship Education; Public Policy; Entrepreneurial Perspective; Entrepreneurial Understanding; Knowledge of Entrepreneurial Skills; Entrepreneurial Attitudes; Entrepreneurial Self-efficacy